Antinociceptive and anti-inflammation activity of P. conoideus lam extract on mice and rats / Ahmad Nashriq Setapa @ Mustapha - Setapa @ Mustapha, Ahmad Nashriq (2008)
Pandanus conoideus Lam is a herb that traditionally used to treat and prevent skin and eye problem, improve stamina and as worm treatment. Due to presence of beta carotene, tokoferol, oleat acid, linoleat acid, linolenat acid, and dekanoat acid it's maybe can be use as anti-nociceptive and anti-inflammatory. So this research was done to evaluate scientifically on the anti nociceptive and anti-inflammation of the Pandanus conoideus Lam oil extract. The anti-nociceptive and anti-inflammation activity are examined using Hot Plate test, Formalin Test and Abdominal Constriction Test. All the test are done either in rat or mice depends on the test that were administered 10 ml/kg 10%, 50% and 100% concentration of extract. For all tests the extract are given by force feeding. Pandanus conoideus Lam was founded to inhibit abdominal constriction and have antinociceptive activity in early phase of formalin test. There was no activity observed during late phase of formalin and hot plate test.